Climate capitalists - Niels Gormsen; Kilian Huber; Sangmin Oh (European Central Bank (ECB), 2024)
Firms' perceived cost of green capital has decreased since the rise of sustainable investing. Green and brown firms perceived their cost of capital to be the same before 2016, but after the post-2016 surge in sustainable investing, green firms perceived their cost of capital to be on average 1 percentage point lower. This difference has widened as sustainable investing has intensified. Within some of the largest energy and utility firms, managers have started applying a lower cost of capital to greener divisions. The changes in the perceived cost of green capital incentivize cross-firm and within-firm reallocation of capital toward greener investments.
Keywords: G10; G12; G31; G32; G41; Q54; 330; Cost of capital; discount rates; sustainable investing; ESG